Genes expression analysis of EgUnk1, EgZFP2, and EgIPK2b in oil palm using Ct value correction and two relative quantification approaches - Riza Arief Putranto; Sudarsono Sudarsono; Sri Wening; Dewi Sukma; Asmini Budiani; Rokhana Faizah (Universitas Gadjah Mada, 2024)
The determination of transcript accumulation values significantly affects gene expression in oil palm. Various genes are involved in pathogen infection, including probable 2‐oxoglutarate‐dependent dioxygenase At5g05600 (EgUnk3), zinc finger protein 2‐like (EgZFP2), and inositol polyphosphate multikinase beta‐like (EgIPK2b). Gene expression is typically measured using relative quantitative methods to calculate differences in quantitative values in the expression levels of targeted genes compared to a reference gene. However, the effectiveness of these methods in assessing the expression of EgUnk3, EgZFP2, and EgIPK2b, which are involved in Ganoderma boninense infection in oil palm seedlings, requires evaluation. This study aimed to establish an effective and straightforward method for analyzing the expression of EgUnk1, EgZFP2, and EgIPK2b genes in oil palm seedlings infected with G. boninense, utilizing Ct value correction through regression coefficients on the 2‐ΔΔCt and E‐ΔΔCt approaches. A correlation regression revealed values of 0.28, ‐0.32, and 0.29 for delta Ct of EgUnk1, EgZFP2, and EgIPK2b, respectively. However, a negative correlation in the Ct mean was corrected by linear regression for the targeted genes: ‐0.55, ‐0.81, and ‐0.29 for EgUnk1, EgZFP2, and EgIPK2b, respectively. The amplification factor (E) and efficiency value (R) using the EgActin gene were 1.95 and 94.92%, respectively. Normalization of log10 on the fold change value 2‐ΔΔCt and 1.95‐ΔΔCt approaches using the regression coefficient yielded consistent results for the EgUnk1, EgZFP2, and EgIPK2b genes. Overall, EgUnk3 and EgIPK2b genes exhibited downregulated expression in susceptible oil palm seedlings (‐0.60 for 2(‐ΔΔCt) and ‐0.58 for 1.95(‐ΔΔCt)), whereas EgIPK2b gene showed up‐regulated and the highest value in inoculated resistant seedlings (1.39 for 2(‐ΔΔCt) and 1.34 for 1.95(‐ΔΔCt)). Basal stem rot disease (BSR) in oil palm decreased EgUnk1 and EgIPK2b expression in susceptible seedlings but increased EgZFP2 gene expression in resistant ones. The results of this research provide valuable corrections to Ct values obtained directly from RT‐qPCR machines using simple linear regression. Consequently, the Ct values of target genes and reference genes exhibit smaller bias values, rendering gene expression levels more reliable.